2018
DOI: 10.1021/acsnano.7b06211
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Boron Nitride: The Thinnest Insulating Barrier to Microbial Corrosion

Abstract: We report the use of a single layer of two-dimensional hexagonal boron nitride (SL-hBN) as the thinnest insulating barrier to microbial corrosion induced by the sulfate-reducing bacteria Desulfovibrio alaskensis G20. We used electrochemical methods to assess the corrosion resistance of SL-hBN on copper against the effects of both the planktonic and sessile forms of the sulfate-reducing bacteria. Cyclic voltammetry results show that SL-hBN-Cu is effective in suppressing corrosion effects of the planktonic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…MIC is a specific type of corrosion where metal deterioration occurs due to microorganisms' metabolic products (i.e., sulfate-reducing bacteria (SRB), sulfur-oxidizing bacteria). Some 2D materials such as graphene, GO, and hBN have exhibited good performance as MIC passivation coating of metals as well as antibacterial coatings [47][48][49][50][51][52][53][54].…”
Section: Petroleum Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…MIC is a specific type of corrosion where metal deterioration occurs due to microorganisms' metabolic products (i.e., sulfate-reducing bacteria (SRB), sulfur-oxidizing bacteria). Some 2D materials such as graphene, GO, and hBN have exhibited good performance as MIC passivation coating of metals as well as antibacterial coatings [47][48][49][50][51][52][53][54].…”
Section: Petroleum Industrymentioning
confidence: 99%
“…Thus, hBN is inherently insulating and does not induce galvanic corrosion. A comparative experimental study between SLG and SL-hBN (i.e., single-layer hBN) on Cu showed that hBN can reduce the galvanic corrosion by nearly 400 times [49]. The galvanic corrosion current density (I g ) and galvanic potential showed a peak during the initial stage of corrosion for SLG (Figure 10a,b).…”
Section: Galvanic Coupling-a Setback For Conductive/metallic 2d Matermentioning
confidence: 99%
“…The 2D material nanocoatings not only mimic the skin's barrier functions but also provide much better and more effective protection against the serious threats that can easily damage human skin. Therefore, 2D materials have attracted great attention in many barrier applications to: (1) impede the penetration of small molecules, (2) mitigate the diffusion of harmful biological substances, and (3) provide high flame resistance …”
Section: D‐material‐based Protective Skinmentioning
confidence: 99%
“…d) Corrosion tests exhibit microbial corrosion resistance of SL‐hBN coatings. c,d) Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: D‐material‐based Protective Skinmentioning
confidence: 99%
See 1 more Smart Citation